Aprimoramento de um elemento estrutural de um motor aeronautico carenado - Naccarato, Alice Petri (Universidade Federal de São Carlos, 2025)
This work presents a study on the sizing and improvement of the fan hub frame of a ducted dual-flow aircraft engine. The study is inserted in the context of the development of more efficient and environmentally responsible engines, in response to the increasing demands for fuel consumption reduction and associated aviation emissions. The project was developed in collaboration with Safran Aircraft Engines and aimed to analyze and improve the geometry of a structural component of the FAN module, seeking to enhance its mechanical behavior without compromising structural integrity. The adopted methodology was based on finite element modeling, through which static structural analyses were performed, including the extreme load case Fan Blade Out (FBO), as well as global stiffness and flexibility analyses of the component. The main geometric parameters and their influence on stresses, displacements, and structural mass were evaluated. The results demonstrated that the proposed improvement was successful, allowing the identification of a configuration that achieves a satisfactory balance between stiffness, flexibility, and mass, meeting the structural requirements of the FAN module.
Improvement of a structural element of an shared aeronautical engine
Keywords: Análise estrutural; Elementos finitos; Motor aeronáutico; Turboélice; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS; 9. Indústria, Inovação e Infraestrutura